Analisis Penyelangaraan Event Motogp dan WSBK Mandalika Terhadap Peningkatan Penjualan Produk UMKM Indonesia - Fanji Farman; Dita Puspitasari; Renalda Adilah Siti Adeni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Indonesia is experiencing an economic recession due to the Covid-19 pandemic, especially the local SME sector which has contracted over the last 3 years, experiencing quite large losses. Therefore, the government is making efforts to restore the national economy, one of which is by holding the 2022-2023 WSBK and MotoGP mega event at the Mandalika circuit in West Nusa Tenggara which is believed to have great potential to have a multiplier effect on the revival of various economic sectors, especially sports in particular Local SME. This research uses a descriptive-qualitative research method using a conceptual framework of the correlation between nation branding and increasing sales of local SME. The results obtained are that the WSBK and MotoGP performances at the Mandalika circuit were able to have a positive impact on various social-economic sectors, especially the local SME sector which participated in promoting local products during the WSBK and MotoGP performances and felt a big impact on increasing income which had contracted due to Covid-19 pandemic. This has become a big momentum for local SME players to increase profits and cover economic losses caused by Covid-19 in the last 3 years.